2021
DOI: 10.1111/1348-0421.12869
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and molecular characterization of chikungunya virus from human cases in North India, 2016

Abstract: Chikungunya virus (CHIKV), an arthropod‐borne Alphavirus is responsible for chikungunya disease. Arthralgia and arthritis are the major symptom. Some patients recover early while others for a very long time. This study provides, epidemiology and molecular characterization of three whole‐genome sequences of CHIKV and assessed phylogenetic analysis, physiological properties, antigenicity, and B‐cell epitope prediction by in silico. We report the clinical epidemiology of 325 suspected patients. Of these, 118 (36.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…At first, the earliest E1-K211E/E2-V264A IOL strain sparsely circulated in Delhi, Mumbai, and Kerala in India since 2010 [25]. Then, the wide expansion of IOL sub-lineage E1-K211E/E2-V264A occurred after the virus acquired the mutation of E1-I317V associated with the later outbreaks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At first, the earliest E1-K211E/E2-V264A IOL strain sparsely circulated in Delhi, Mumbai, and Kerala in India since 2010 [25]. Then, the wide expansion of IOL sub-lineage E1-K211E/E2-V264A occurred after the virus acquired the mutation of E1-I317V associated with the later outbreaks.…”
Section: Discussionmentioning
confidence: 99%
“…Although IK-b Kenya strains were most closely related to the Indian strains 2014 (KX619422and KX619423), they shared E1-K211E and E2-V264A in common, the long branch between IK-b and New Delhi 2014 suggested possible missing sampling of circulating strains in this gap. In addition, there were nonsynonymous mutations (nsP1-V139I, nsP2-V793I, E1-I344M, E3-T23S) specific to the IK-b clade, indicating a unique evolution of the Kenya 2016 viruses[25].…”
mentioning
confidence: 99%
“…Using a bacteriophage Qβ viruslike particle (VLP) platform, Basu et al reported that epitopes spanning 1–18 and 226–259 aa elicited high-titer antibodies and the C-terminal epitope (spanning 378–411 aa) was the least reactive, possibly due to the truncated E2 protein fragment used in this study . In an in silico B-cell epitope prediction study, the epitope residues at 386 and 388 aa positions were predicted to evoke significant immune response . Of note, an immuno-informatics study by Hasan et al reported the peptide region spanning 9 aa from 397 to 405 aa as the most potential B-cell epitope, along with epitopes identified in the N-terminal region (1–29 aa) .…”
Section: Discussionmentioning
confidence: 77%
“…57 In an in silico B-cell epitope prediction study, the epitope residues at 386 and 388 aa positions were predicted to evoke significant immune response. 58 Of note, an immuno-informatics study by Hasan et al reported the peptide region spanning 9 aa from 397 to 405 aa as the most potential B-cell epitope, along with epitopes identified in the N-terminal region (1−29 aa). 59 Rodriguez et al also predicted B-cell epitopes located in the N-terminal (spanning 14−22 and 27−35 aa) and C-terminal (spanning 367−389 aa) regions, suggesting that the presence of these amino acids in the CHIKV E2-FL protein may be contributing in its increased immunogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…The E2-L248F from clade I has been reported in Asian lineage sequences from Colombia (2014-2015) and Philippines (2012) 45,46 . Isolates from Thailand, Indonesia, Lao PDR, Cameroon and India also presented the 6K-I54V mutation observed in clade I 44,[47][48][49][50] .…”
Section: Discussionmentioning
confidence: 92%